STUDIES ON A NEW SPECIES OF MYXIDIUM (PROTOZOA : MYXOZOA : MYXOSPOREA) FROM A FRESHWATER TELEOST FISH CIRRHINA REBA (HAM) - ., YATINDRA; MATHUR, B. N. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
A new species of myxosporean, Myxidium nolnari ni sp infecting the gall-bladder of Cirrhina reba is described. A comparative morphometrics of all the species of Myxidium reported from fishes of India is also given.